Effects of nonprotein amino acids on survival and locomotion of Osmia bicornis. Issue 5 (27th June 2018) - Felicioli, A.; Sagona, S.; Galloni, M.; Bortolotti, L.; Bogo, G.; Guarnieri, M.; Nepi, M.
Abstract: To investigate the effects of two nectar nonprotein amino acids, β‐alanine and γ‐aminobutyric acid (GABA), on Osmia bicornis survival and locomotion, two groups of caged bees were fed with sugar syrup enriched with β‐alanine and GABA, respectively. A further control group was fed with sugar syrup. Five behavioural categories were chosen according to the principle of parsimony and intrinsic unitary consistency from start to end, and recorded by scan sampling: two states (remaining under paper or in tubes) and three events (walking on net, feeding from flower and flying). We also analysed the amino acid content of haemolymph sampled from an additional 45 bees fed the same diets (15 per diet type). Bees fed with β‐alanine had a significantly shorter survival time than those fed with the control and GABA diets. The GABA diet induced higher levels of locomotion than β‐alanine. The former nonprotein amino acid was only detected in the haemolymph of bees fed GABA. The results suggest that insects consuming nonprotein amino‐acid‐rich diets absorb and transfer these substances to the haemolymph and that nonprotein amino acids affect survival and locomotion. Ecological consequences are discussed in the framework of plant reproductive biology.